The Role of Social Worker in the Context of Refugees and Asylum Seekers Rights in Indonesia - Alamsyah; Intan Slipi Lia; Muh. Akbar (Jurnal Ilmu Hubungan Internasional LINO, 2020)
The plight of refugees and asylum seekers has been a global issue of critical importance for social workers in Indonesia. At the end of February 2018, the public was overwhelmed by mass media coverage of the large number of refugees living on the streets in front of the Immigration Office in Jakarta. In fact, many of the difficulties experienced by them in Indonesia, such as legal status, poor detention and others. Their existence needs to be noticed by the government and be a very important concern for social workers in Indonesia. Social workers are often compromised in working with refugees and asylum seekers to successful social functioning. This paper presents mixed methodology through individual interviews and an exploratory study in which social workers play a pivotal role in responding to the issues as well as potential way for being supporting document for Indonesian government to ratify the 1951 Refugee Convention. Keywords: Refugees, Asylum Seekers, Social Worker, Social Functioning, 1951 Refugee Convention